Permasalahan dan Rumusan Perbaikan Pengelolaan Dana Penelitian di Indonesia - Dalilah, Elih; Pratama, Fitrah (Komisi Pemberantasan Korupsi, 2020)
Even though 2019 Indonesia’s research fund rising to 0.28% of GDP, its expenditure is dominated by operational cost rather than to actual research cost. The operational cost is also tended to skyrocket from 2016 and reach 47.22% of the total cost in 2019. Besides the allocation inappropriateness, research fund is allegedly misused in forms of fictitious research, overlapped activities, fund reduction to 10%-50%, unregulated allocation and use, and budget deposition. Therefore, Corruption Eradiacation Commission was conducting a study using policy research based on qualitative approach in order to identify problems and formulate research policy corrective recommendation. Based on the study, the main research problems experienced by Indonesia was caused by the absence of detailed standard regarding to definition, sources, use mechanism, budget monitoring of research fund as well as the unclear research expenditure component. These problems potentially escalate the researcher’s mens rea to manipulate their research activities. Therefore, the government and stakeholders are encouraged to regulate in detail including those problems which is applied to all research institution.